Ṣabrah, a satellite hamlet of Petra - Tholbecq, Laurent; Fournet, Thibaud; Paridaens, Nicolas; Delcros, Soline; Durand, Caroline (Proceedings of the Seminar for Arabian Studies, 2016)
This paper aims to provide the first reassessment of the available documentation concerning the Nabataean-Roman site of Ṣabrah, situated in Wādī Ṣabrah, 6.5 km south of Petra. A major sanctuary developed at the latest between the first and early fourth century AD, together with major adjacent structures such as a bath-house and a theatre, in a small oasis situated on a track joining Wādī ʿArabah to the Nabataean capital and supplied by spring and rainfall water. For the first time since its discovery in 1828, a 1:50 top plan of its visible remains has been drawn. Along with a general description and surface ceramic material, it gives a first general image of the site and serves as the basis for renewed analysis.